Constructed wetland challenges for the treatment of industrial wastewater in smart cities: A sensitive solution. (February 2023) - Hota, Amrutashree; Gopal Krishna Patro, S; Obaid, Ahmed J.; Khatak, Satish; Kumar, Raghvendra
Highlights: Constructed Wetland in the application of Industrial wastewater. Constructed Wetlands treats and manages the wastewater in smart cities. Medicinal Culture in constructed wetlands. Medicinal knotweed plant for the treatment and degradation of dye and heavy metals. Sustainability of constructed wetlands. Abstract: Since last few years, the Constructed Wetlands (CWs) are being employed as a green as well as sustainable method to treat different types of wastewater released from industrial sources in smart cities. Particularly for small villages and isolated areas, CWs provide an energy- and land-efficient alternative to traditional treatment systems. There are still many questions regarding the effective implementation of these systems and their long-term viability. This study aims to offer and inspire sustainable options for the effectiveness and use of CWs by thoroughly evaluating their application and the most recent developments in their sustainable design and operation for wastewater treatment. First, a brief explanation of the definition, classification, and application of current CWs has been given. The relationship between the operational needs and design criteria of CWs, such as substrate types, hydraulic retention time, water depth, plant species, hydraulic load, and feeding mechanism, and the operation's sustainability for treating wastewater has then been examined. Growing knotweed plants, which bind dye particles in the soil and take up heavy metal ions for better growth, as well as reducing the detrimental effects of dyes and heavy metals, are some of the sustainability initiatives for those wetland technologies that are outlined in this paper. If employed, this approach can clean wastewater in smart cities and metropolitan regions that are polluted by industrial waste water very well with a single expenditure. Future research on improving the sustainability and stability of CWs is also emphasised as being crucial.